To ‘dump’ or not to ‘dump’: changing, supporting or distracting behavior - Kamaruddin, Azrina; Dix, Alan (IEEE, 2010)
The way we manage our personal information varies considerably between users. An exploratory study was conducted to investigate the decision making process when storing new items and in particular their dumping behavior, which we define as putting in some unclassified/partially classified storage. It was found that users 'dump' when unsure where to store, do not have the time to decide where to store, or not want to lose sight of data - these all have an impact on future retrieval. Understanding this behavior suggests design opportunities to support users, raising awareness of previously encountered but dumped information.